Morphological traits and type of dairy goats registered in Brazil from 1976 to 2009 - Ferreira, Talita Andrade; Pereira, Idalmo Garcia; Guimaraes Gouveia, Aurora Maria; Pires, Aldrin Vieira; Faco, Olivardo; Meira, Camila Tangari [UNESP]; Furusho Garcia, Iraides Ferreira; Souza Lima Mattos de Paiva Guimaraes, Maria Pia (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2013)
Data from 2439 goats of the Saanen, Alpine, Anglo Nubian and Toggenburg breeds recorded from 1976 to 2009 by the Association of Goats and Sheep Breeders of Minas Gerais were used in principal component analysis. After consistency of data, six morphological variables (thorax perimeter, body length, withers height, height, width and length of the rump) and 12 variables related to breed standard score and fitness (breed characteristic, head, palette and topline, feet and legs, dairy type, body capacity, udder, rear and front ligament, udder texture, teat and final score) were analyzed. Based on the magnitude of the eigenvalue (lower than 0.7), eleven variables considered redundant were discarded, resulting in reduced costs of technician labor to evaluate the animals. Maintenance of records on height, length, rump width, breed characteristic, dairy type, front ligament and udder texture is recommended.
Keywords: correlation; discard of variable; Goat; Multivariate analysis